A novel exaggerated "spino-bulbo-spinal like" reflex of lower brainstem origin. (April 2019) - Merchant, Shabbir Hussain; Vial, Felipe; Leodori, Giorgio; Fahn, Stanley; Pullman, Seth L.; Hallett, Mark
Abstract: Background: Many different oligosynaptic reflexes are known to originate in the lower brainstem which share phenomenological and neurophysiological similarities. Objective: To evaluate and discuss the differences and aberrancies among these reflexes, which are hard to discern clinically using neurophysiological investigations with the help of a case report. Methods: We describe the clinical and neurophysiological assessment of a young man who had a childhood history of opsoclonus-myoclonus syndrome with residual mild ataxia and myoclonic jerks in the distal extremities presenting with subacute onset total body jerks sensitive to sound and touch (in a limited dermatomal distribution), refractory to medications. Results: Based on clinical characteristics and insights gained from neurophysiological testing we could identify a novel reflex of caudal brainstem origin. Conclusions: The reflex described is likely an exaggerated normal reflex, likely triggered by a dolichoectatic vertebral arterial compression and shares characteristics of different reflexes known to originate in caudal brainstem, which subserve distinctive roles in human postural control. Highlights: Different brainstem reflexes serve distinctive roles in postural and motor control. Phenomenological and physiological differences are hard to discern clinically. We describe a novel brainstem reflex in humans using neurophysiological techniques. Reflex shares characteristics with other normal reflexes of caudal brainstem origin.